Gadgets and their importance in our life - Vuchurova, A. (ТДАТУ, 2018)
EN: This report is devoted to the influence of gadgets on the health and daily life of a person. The world is developing very quickly and we must be aware of the latest discoveries and inventions. Modern progress and technology development surround us. In this report we want to introduce some modern gadgets and discoveries in science. Also showing how modern companies promote application of advanced technology for improving the performance and value addition to existing technology. We showed several aspects of the impact of modern technology on humans and indicated ways to reduce the negative impact. In addition to new technologies, we want to share our personal research how our gadgets affect us, especially our phones. UK: Цю статтю присвячено впливу гаджетів на здоров'я та повсякденне життя людини. У статті представлено деякі сучасні гаджети та відкриття в науці. Також показано, як сучасні компанії сприяють застосуванню передових технологій для підвищення продуктивності та додавання вартості до існуючих технологій. Ми продемонстрували кілька аспектів впливу сучасних технологій на людину та вказали способи зменшення негативного впливу. Окрім нових технологій, ми хочемо поділитися нашими особистими дослідженнями, як наші гаджети впливають на нас, особливо наші телефони.
Keywords: гаджети; gadgets; застосування передових технологій; вплив сучасних технологій на людину; advanced technology; impact of modern technology on humans